A REVIEW OF FAMILY DEMOGRAPHICS AND FAMILY POLICIES IN THE NORDIC COUNTRIES - Grødem, Anne Skevik (Baltic Journal of Political Science, 2015)
The aim of this article is to review key aspects of family demographics and family policies in Sweden, Denmark, Finland, Norway and Iceland, and discuss similarities and differences between the five countries. After a brief historical sketch, some aspect s of family demographics – union formation and dissolution, fertility, and female employment rates – are presented. The main part of the article reviews family policies: family benefits, parental leaves, public child-care and financial support for home-based care. The article ends with a discussion of future challenges for Nordic family policies, and the potential for policy transfer. It is emphasised that the “Nordic model” of family policy is a model with at least four faces: the “low-key” Finnish version, the maximalist equality-and-choice-oriented Norwegian version, the Swedish dual earner/dual carer version and the universal employment-oriented Danish version.